Forced swim test in mice: A common animal model of depression (Bangladesh Journal of Pharmacology, 2015)
The Forced Swim Test (FST) is a rodent behavioral paradigm utilized for assessment of potential antidepressant-like medications. In this model the mice are put in a plexiglas tank. The tank is loaded with water and the behavior of the mice to escape the tank is scored. The behavioral parameter scored in this test is called immobility, resembling a behavioral state of misery, as seen in human depression.Video Clip of Methodology: Pre-experiment:  50 sec   Full Screen   AlternateExperiment: 7 min 12 sec   Full Screen   Alternate